Mencegah Pernikahan Dini untuk Menanggulangi Stunting di Kalangan Generasi Muda Kecamatan Keruak - Agus Kurnia; Putri Hajar Aswat; Az Zaky Hanif; Fathiyya Ari Mufidah; M. Abiyyu Shamid; Fadhila Astagina Maharani (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2025)
Early marriage is a problem that still occurs in West Nusa Tenggara, with East Lombok accounting for 58.1% of cases and ranking second in the province. This phenomenon contributes to the high stunting rate, especially in Keruak District, which recorded 993 stunting cases related to early marriage. This service activity aims to increase the awareness of students at SMKN 1 Keruak about the dangers of early marriage and its impact on stunting. The methods used include counseling, interactive discussions, and training. The results showed an increase in students' knowledge about the risks of early marriage and its impact on children's health. Proper education can change the views of adolescents and contribute to stunting prevention. The significance of this activity lies in raising awareness among adolescents, which is expected to continue through sustainable programs in the future.